Promoting solar irrigation service providers in Ganga basin: jobs, affordable irrigation and accelerated green revolution - Shah, Tushaar; Verma, Shilp; Rai, Gyan Prakash; Durga, Neha (2018)
The plains of the Ganga-Brahmaputra-Meghna (GBM) basin, encompassing Bangladesh, Nepal terai and eastern India, are home to a quarter of the world’s rural poor. The basin’s copious aquifers are the biggest hope for millions of smallholders locked into unviable agriculture. Studies suggest shallow groundwater wells can support 2.5 crops/year in much of the basin without threat of depletion. Yet, cropping intensities hover around 1.2- 1.5 in most parts. Rapid expansion in shallow tubewell irrigation has begun to show productivity improvement for tubewell owners, but marginal farmers and tenants remain in a disadvantageous position in this tubewell irrigation economy.